"Dominion Theology" and Ressentiment: A Genealogy of the Relationship Between Religion and Politics Based on Brazil's Recent History - Alvarenga, Leonardo (2025)
The text analyzes Dominion Theology, a religious interpretation seeking to impose biblical laws on Brazil, including harsh punishments and restrictions on individual freedoms. The analysis is grounded in Nietzsche and Foucault's genealogical method, which aims to uncover the origins and power mechanisms behind ideas. The text argues that Dominion Theology is not merely a political strategy but an expression of resentment among evangelical groups feeling marginalized in a secular state. By seeking political control, these groups would invert values and exercise power in a covert manner, even within democratic frameworks. The central thesis is that resentment is the driving force behind Dominion Theology, propelling the pursuit of totalitarian control and the imposition of a fundamentalist religious worldview on society.